Diatrack particle tracking software: Review of applications and performance evaluation. (23rd October 2017) - Vallotton, Pascal; van Oijen, Antoine M.; Whitchurch, Cynthia B.; Gelfand, Vladimir; Yeo, Leslie; Tsiavaliaris, Georgios; Heinrich, Stephanie; Dultz, Elisa; Weis, Karsten; Grünwald, David
Abstract : Object tracking is an instrumental tool supporting studies of cellular trafficking. There are three challenges in object tracking: the identification of targets; the precise determination of their position and boundaries; and the assembly of correct trajectories. This last challenge is particularly relevant when dealing with densely populated images with low signal‐to‐noise ratios—conditions that are often encountered in applications such as organelle tracking, virus particle tracking or single‐molecule imaging. We have developed a set of methods that can handle a wide variety of signal complexities. They are compiled into a free software package called Diatrack. Here we review its main features and utility in a range of applications, providing a survey of the dynamic imaging field together with recommendations for effective use. The performance of our framework is shown to compare favorably to a wide selection of custom‐developed algorithms, whether in terms of localization precision, processing speed or correctness of tracks. Abstract : In digital microscopy, it is often necessary to track and quantify the motion of moving targets such as endosomes, viral particles or single molecules. In this Toolbox article, the Diatrack object tracking software is introduced and shown suitable for a wide array of scenarios. Application to movies of simulated targets in controlled conditions is used to demonstrate the framework's performance on an objective basis. Extensive literature references are provided that illustrate best practices in using the software.